Redesain Sistem Pengangkatan dan Pemberhentian Hakim di Indonesia - Idul Rishan (Fakultas Hukum Universitas Islam Indonesia, 2016)
This study reviews the redesign of the appointment and dismissal of judges in Indonesia. This is a prescriptive-normative judicial research conducted using the legislation approach, historical approach, and conceptual approach. The study concluded that the redesign of the judge appointment and dismissal system can be formulated with a variety of formulations. First, it is by organizing a constitutional basis to realign the will of judicial independence and by acknowledging the existence of an independent state organ in the constitution to rearrange the complicated power relations of the Supreme Court, the Judicial Commission and the Constitutional Court. Second, it is by carrying out the merit in the judge appointment system to maintain the constellation of the checks and balances principle. After reforming the mechanism of judge appointment, then the third one is by initiating the course of judge impeachment in an integrative manner as a form of accountability of the judiciary power in the non-judicial realm.